Novel insights into the adsorption of organic contaminants by biochar: A review. (January 2022) - Luo, Zirui; Yao, Bin; Yang, Xiao; Wang, Lingqing; Xu, Zhangyi; Yan, Xiulan; Tian, Lin; Zhou, Hao; Zhou, Yaoyu
Abstract: With rising concerns in the practical application of biochar for the remediation of environment influenced by various organic contaminants, a critical review to facilitate insights the crucial role that biochar has played in wastewater and polluted soil decontamination is urgently needed. This research therefore aimed to describe different intriguing dimensions of biochar interactions with organic contaminants, which including: (i) an introduction of biochar preparation and the related physicochemical properties, (ii) an overview of mechanisms and factors controlling the adsorption of organic contaminants onto biochar, and (iii) a summary of the challenges and an outlook of the further research needs in this issue. In the light of the survey consequences, the appearance of biochar indicates the potential in substituting the existing costly adsorbents, and it has been proved that biochar is one promising adsorbent for organic pollutants adsorption removal from water and soil. However, some research gaps, such as dynamic adsorption, potential environmental risks, interactions between biochar and soil microbes, novel modification techniques, need to be further investigated to facilitate its practical application. This research will be conductive to better understanding the adsorption removal of organic contaminants by biochar. Graphical abstract: Image 1 Highlights: The roles of biochar in organic pollutants adsorption are reviewed. Relationships between preparation conditions and biochar properties are studied. Key factors influencing biochar adsorption performances are discussed. Biochar adsorption is a complicated process involved in different mechanisms. The improved achievements and future research needs are highlighted.